Development of the traceability system for the pasta production - Drychyk, Mariia; Shulga, Oksana (My University, 2022)
The traceability system is a necessary component for identification the market operator, time, place, an object and other conditions of supply (sale or transfer) sufficient to establish the food origin, materials in contact with food products, or substances intended to be included, or expected to be included in the recipe of food, at all production stages, processing and circulation. The Law of Ukraine «On Basic Principles and Requirements for the Safety and Quality of Food» clause 74 of Article 1, Regulation (EC) No. 178/2002 and ISO 22005:2007 and CAC/GL 60-2006 and GS1 provide general requirements for traceability systems, however, each branch of the food industry has its own specifics regarding the implementation of the traceability system. The article presents the results of the traceability development for pasta production. There is the block traceability diagram production for pasta production, the plan of the internal system and tools for the traceability system implementation are proposed. Implementation of the traceability system for pasta production will allow solving the following tasks: identifying partners in the food chain; carry out a quick search for pasta dangerous for nutrition; control all product components and the entire food chain; promptly remove pasta products from circulation when there is a threat to the consumers health; ensure compliance with specifications; provide an opportunity for the market operator to achieve compliance with the requirements of legislation and regulatory documents; achieve effective management of supply logistics as a whole; help the consumer to get information about raw materials, product composition and production method; perform upward tracing from the consumer to the producer and downward tracing from the producer to the consumer.

Впровадження системи простежуваності на макаронному виробництві дозволить вирішити такі завдання: ідентифіковувати партнерів в харчовому ланцюгу; здійснювати швидкий пошук небезпечних макаронних виробів; контролювати усі складники продукту та весь харчовий ланцюг; оперативно вилучати макаронні вироби з обігу під час виникнення загрози здоров'ю споживачів; забезпечувати відповідність специфікаціям; надавати можливість оператору ринку досягнути відповідність вимогам законодавства та нормативних документів; досягти ефективного управління логістикою постачань в цілому; допомагати споживачу отримати інформацію про сировину, склад продукту та спосіб виробництва; здійснювати висхідне простеження від споживача до виробника та низхідне простеження від виробника до споживача.
Keywords: кафедра експертизи харчових продуктів; market operator; traceability; pasta; safety; простежуваність; макарони; безпечність; оператор ринку